2021
DOI: 10.1186/s12885-021-09069-9
|View full text |Cite
|
Sign up to set email alerts
|

Mirogabalin vs pregabalin for chemotherapy-induced peripheral neuropathy in pancreatic cancer patients

Abstract: Background The prognosis of pancreatic cancer (PC) has been improved by new chemotherapy regimens (combination of 5-fluorouracil, oxaliplatin, irinotecan, and leucovorin (FOLFIRINOX) or gemcitabine plus nab-paclitaxel (GnP)). Unfortunately, chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse event of these two regimens. The efficacy of pregabalin for CIPN has been reported in previous studies. However, the efficacy of mirogabalin for CIPN remains unknown. Thus, in this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
(43 reference statements)
1
12
1
2
Order By: Relevance
“…Pregabalin is a well-known anti-epileptic and analgesic drug that has been one of the staples in the treatment of neuropathic pain for years. Pregabalin was effective in ameliorating CIPN in numerous clinical trials of cancer-related neuropathic pain and allodynia after treatments with vincristine, paclitaxel, and drug cocktails comprising oxaliplatin (Atreya, 2016;Avan et al, 2018;Mishra et al, 2012;Sugimoto et al, 2021). However, data regarding its effectiveness in the treatment of cold allodynia are more controversial: earlier clinical trials and case studies found clear effectiveness of pregabalin to treat oxaliplatin-dependent neuropathy, whereas a more recent double-blinded trial found no significant difference from placebo on oxaliplatin-dependent CIPN, and ASCO guidelines do not fully recommend the use of gabapentinoids to treat CIPN (de Andrade et al, 2017;Loprinzi et al, 2020;SAIF et al, 2010).…”
Section: Oxaliplatin Mediates a De Novo Sensitization Of Previously S...mentioning
confidence: 99%
“…Pregabalin is a well-known anti-epileptic and analgesic drug that has been one of the staples in the treatment of neuropathic pain for years. Pregabalin was effective in ameliorating CIPN in numerous clinical trials of cancer-related neuropathic pain and allodynia after treatments with vincristine, paclitaxel, and drug cocktails comprising oxaliplatin (Atreya, 2016;Avan et al, 2018;Mishra et al, 2012;Sugimoto et al, 2021). However, data regarding its effectiveness in the treatment of cold allodynia are more controversial: earlier clinical trials and case studies found clear effectiveness of pregabalin to treat oxaliplatin-dependent neuropathy, whereas a more recent double-blinded trial found no significant difference from placebo on oxaliplatin-dependent CIPN, and ASCO guidelines do not fully recommend the use of gabapentinoids to treat CIPN (de Andrade et al, 2017;Loprinzi et al, 2020;SAIF et al, 2010).…”
Section: Oxaliplatin Mediates a De Novo Sensitization Of Previously S...mentioning
confidence: 99%
“…Oszacowano, że po upływie 1 roku ból nadal występuje u 3% pacjentów. W leczeniu objawowym pierwszego rzutu stosuje się: doustne trójcykliczne leki przeciwdepresyjne, pregabalinę, opioidy oraz miejscowo lidokainę 5%, kapsaicyne [18]. Kato i współpracownicy w 2019 r. zbadali skuteczność oraz bezpieczeństwo mirogabaliny w leczeniu neuralgii popółpaścowej.…”
Section: Neuralgia Popółpaścowaunclassified
“…Przeprowadzono również badanie, w którym zastosowano mirogabalinę jako koanalgetyk w bólach przebijających w chorobie nowotworowej. Okazała się ona skuteczna u 88,2% pacjentów [18]. Nie wykazano korzystnego działania w zwalczaniu bólu w przebiegu fibromialgii [24].…”
Section: Wnioskiunclassified
“…Previously, mirogabalin was used for diabetes-related peripheral neuropathy 61) . We have reported on the efficacy of mirogabalin for CIPN in PC patients 62) . In the study, 163 PC patients received FOLFIRINOX or GnP therapy.…”
Section: Drug Treatmentmentioning
confidence: 99%